10r/8r+3 - 2r - 3/8r + 3 =?

Hi Jamal. Here's how I would approach this problem. First, let's write it out a little more clearly, so we can see what we're doing a little better. (10r/8r) + 3 - 2r - (3/8)r + 3 = ? OK. Now, what can we simplify? "Simplify" is a sneaky word in mathematics. It means . . . do some math! Let's start by grouping together like terms. (10r/8r) + 3 - 2r - (3/8)r +3 = ? (10/8)r - (3/8)r -2r + 3 + 3 = ? (7/8)r -2r + 6 = ? That looks a little more manageable, doesn't it? Try re-writing 2r as (16/8)r and see if you can simplify any further. Good luck, Jamal!